Strategi Bertahan Agama Djawa Sunda (ADS) Cigugur - Qodim, Husnul (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2017)
The local religion is one of the themes that is still important for the study. One of the local religions in West Java is Agama Djawa Sunda (Religion of Java Sunda). As a religious community in Indonesia, Agama Djawa Sunda (ADS) community is minority group category, beside they faced the prohibition from the state; they also received the discriminative acts from the majority groups. The question is how the strategy of ADS community to maintain their beliefs existence after the state prohibition. The research is qualitative approach using descriptive method. The data collection techniques are using field in-depth interview, observation and literary study related to the topic. The result of research concluded that ADS community has succeeded to maintain their beliefs existence from any threats and challenges of the majority group. There are three strategies to maintain: first, they have obeyed the state prohibition and converted under the subordination of formal religion, but they voiced for negotiating infinitely (‘voice’); second, they have reorganized repeatedly based on the ‘secure’ situation and the context of power played; third, they have reconstructed their early identity to a new identity, in early as the identity of beliefs being to the identity of custom.